Training on "E-Commerce and Digital Marketing Designs" (E- Codigimark) to Support the System Economy Village as a Form of Community Empowerment in Puger Kulon Village, Jember Regency - Sintiawati, Nani; Muhammad Irfan Hilmi; Karina Nine Amalia; Viona Nadya Fernanda; Mukhammad Yafi’ Istiqlal; Rifda Nurul Azmi; Evianta Rifka Yulistia; Ahmad Ilyas (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Economic growth in rural areas relies on managing natural and economic resources, emphasizing local wisdom. Village-owned Enterprises (BUMDes) is crucial in mobilizing local potential and improving infrastructure to support micro, small, and medium enterprises (MSMEs). In Puger Kulon Village, known for its fisheries and unique MSME products like shrimp paste and handicrafts, the lack of digital marketing limits economic growth. This community service aims to empower local MSMEs through E-CoDigimark, a digital platform that enchances product promotion and accessibility. Activities included socialization, training in website management, and digital marketing workshops. MSME actors learned to utilize social media, marketplaces, and E-CoDigimark to market their products effectively. Mentoring sessions prepared local admins to manage the platform sustainably. As a result, local businesses gained better visibility, and MSMEs improved their skills in creating engaging content, managing online stores, and connecting with broader markets. The program significantly impacted local economic empowerment, improving product competitiveness and digital marketing capabilities. With E-CoDigimark, Puger Kulon’s products now reach national and global markets, fostering sustainable economic development and establishing the village as a center of tourism and local enterprise.